Perspective on the Development and Validation of Ab Reagents to Fish Immune Proteins for the Correct Assessment of Immune Function - Dixon, Brian; Barreda, Daniel R.; Sunyer, J. Oriol (Frontiers in Immunology, 2018)
Understanding of immune function in humans and model organisms, such as mice, has advanced in the last few decades because of technological breakthroughs and availability of reagents. While novel genomic technologies have helped to increase knowledge of many aspects of immunology, most developments in immunology have occurred because of the availability of antibodies to identify and sort different cell types, as well as to identify and quantify the protein products of cells. Unfortunately, many studies performed in fish make use of poorly characterized antibody reagents that may affect the conclusions of those studies. In light of this, we would like to offer some insight and discussion points based on our research experience on the strategies and techniques that are required for proper validation of antibody reagents to fish immune molecules. Our main goal is to encourage a much needed discussion in our field to foster the use of correctly validated reagents that enable the study of fish immune function.